Efficacy of a Student-Led, Community-Based, Multifactorial Fall Prevention Program: Stay in Balance - Der Ananian, Cheryl A.; Mitros, Melanie; Buman, Matthew Paul (Frontiers in Public Health, 2017)
Background Falls are a major public health concern in older adults. Recent fall prevention guidelines recommend the use of multifactorial fall prevention programs (FPPs) that include exercise for community-dwelling older adults; however, the availability of sustainable, community-based FPPs is limited. Methods We conducted a 24-week quasi-experimental study to evaluate the efficacy of a community-based, multifactorial FPP [Stay in Balance (SIB)] on dynamic and functional balance and muscular strength. The SIB program was delivered by allied health students and included a health education program focused on fall risk factors and a progressive exercise program emphasizing lower-extremity strength and balance. All participants initially received the 12-week SIB program, and participants were non-randomly assigned at baseline to either continue the SIB exercise program at home or as a center-based program for an additional 12 weeks. Adults aged 60 and older (n = 69) who were at-risk of falling (fall history or 2+ fall risk factors) were recruited to participate. Mixed effects repeated measures using Statistical Application Software Proc Mixed were used to examine group, time, and group-by-time effects on dynamic balance (8-Foot Up and Go), functional balance (Berg Balance Scale), and muscular strength (30 s chair stands and 30 s arm curls). Non-normally distributed outcome variables were log-transformed. Results After adjusting for age, gender, and body mass index, 8-Foot Up and Go scores, improved significantly over time [F(2,173) = 8.92, p = 0.0; T0 − T2 diff = 1.2 (1.0)]. Berg Balance Scores [F(2,173) = 29.0, p < 0.0001; T0 − T2 diff = 4.96 (0.72)], chair stands [F(2,171) = 10.17, p < 0.0001; T0 − T2 diff = 3.1 (0.7)], and arm curls [F(2,171) = 12.7, p < 0.02; T0 − T2 diff = 2.7 (0.6)] also all improved significantly over time. There were no significant group-by-time effects observed for any of the outcomes. Conclusion The SIB program improved dynamic and functional balance and muscular strength in older adults at-risk for falling. Our findings indicate continuing home-based strength and balance exercises at home after completion of a center-based FPP program may be an effective and feasible way to maintain improvements in balance and strength parameters.